Epithelioid and Clear Cell Solitary Fibrous Tumors: Clinicopathologic, Immunohistochemical, and Molecular Genetic Study of 13 Cases. (18th October 2022) - Suster, David I.; Mackinnon, Alexander C.; Mejbel, Haider A.; Gross, John M.; Suster, Saul
Abstract : Solitary fibrous tumors (SFTs) are ubiquitous soft tissue neoplasms known for their protean histology and potentially aggressive behavior. Although most cases are composed of a monotonous proliferation of spindle cells, some tumors show unusual cytologic features. We have studied 13 SFTs that were characterized by a predominant population of round epithelioid cells with abundant eosinophilic cytoplasm and clear cell changes. The tumors occurred in 8 women and 5 men, aged 36 to 80 years (mean=63 y), and were located within the orbit (3), lower extremity (3), retroperitoneum (2), abdominal cavity (2), and superficial soft tissues of the neck, pelvis, and pubis (1 each). The tumors measured from 3.5 to 24.5 cm. Using a risk assessment system, 6 cases were stratified as low-risk tumors; 3 of these showed no evidence of recurrence or metastases from 6 to 18 years, and 1 tumor in the orbit recurred and led to the patient's demise. Five cases were of intermediate risk; clinical follow-up showed no evidence of recurrence or metastases from 3 to 4 years in 3 patients, and 1 patient suffered a recurrence 4 years after diagnosis. Two cases were high risk; 1 patient died after 1 year and the second patient experienced local recurrence at 4 years. Immunohistochemical studies showed nuclear positivity for STAT6 in 10 cases. CD34 immunohistochemistry was positive in 11 cases. A NAB2::STAT6 rearrangement was present in all cases. Epithelioid and clear cell SFT should be considered in the differential diagnosis of soft tissue neoplasms with epithelioid and clear cell morphology.